Bellomo, Manlio. Saggio sull' Universitá nell' etá del diritto comune. Roma: Il Cigno Galileo Galilei, 1999,284 pp. - Hubeñak, Florencio (2000)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina